Lessons learned from COVID-19 for the post-antibiotic future - Wilson, Lindsay A; Rogers Van Katwyk, Susan; Fafard, Patrick; Viens, A. M; Hoffman, Steven J (Université d'Ottawa | University of Ottawa, 2020)
Abstract Introduction COVID-19 has rapidly and radically changed the face of human health and social interaction. As was the case with COVID-19, the world is similarly unprepared to respond to antimicrobial resistance (AMR) and the challenges it will produce. COVID-19 presents an opportunity to examine how the international community might better respond to the growing AMR threat. Main body The impacts of COVID-19 have manifested in health system, economic, social, and global political implications. Increasing AMR will also present challenges in these domains. As seen with COVID-19, increasing healthcare usage and resource scarcity may lead to ethical dilemmas about prioritization of care; unemployment and economic downturn may disproportionately impact people in industries reliant on human interaction (especially women); and international cooperation may be compromised as nations strive to minimize outbreaks within their own borders. Conclusion AMR represents a slow-moving disaster that offers a unique opportunity to proactively develop interventions to mitigate its impact. The world’s attention is currently rightfully focused on responding to COVID-19, but there is a moral imperative to take stock of lessons learned and opportunities to prepare for the next global health emergency.